PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PEMALSUAN MEREK PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 15 TAHUN 2001 TENTANG MEREK - Alimuddin Sinurat; Runtung Runtung; Suhaidi Suhaidi; Mahmud Mulyadi (USU LAW JOURNAL, 2014)
ABSTRACT   In Law No. 15/2001 on brand, the caharacteristics of the criminal act of brand counterfeiting belong to the statement that all criminal act of brand counterfeiting is a violation that it is more to private than public law in nature, the characteristic of criminal law is increasingly less raised, the ordinary offense is changed into a crime on complaint, and the imprisonmentis reduced from 7 years to a maximum of 5 years. The law enforcement resulted in the uncertainty of law and justice. Different court decisions based on different criminal charge and even different imposed articles are given to the matters of the same cases. Therefore, the crime on complaint shall be changed into ordinary offense and the criminal act of brand counterfeiting shall also be considered as a criminal act not as a violation only.   Keywords: Brand, Characteristics, Criminal Act, Brand Counterfeiting, Law Enforcement